Comparison of adhesion layers of gold on silicate glasses for SERS detection. (23rd October 2015) - Colas, F; Barchiesi, D; Kessentini, S; Toury, T; Chapelle, M Lamy de la
Abstract: Gold is one of the most widely used metals for building up plasmonic devices. Although slightly less efficient than silver for producing sharp resonance, its chemical properties make it one of the best choices for designing sensors. Sticking gold on a silicate glass substrate requires an adhesion layer, whose effect has to be taken into account. Traditionally, metals (Cr or Ti) or dielectric materials (TiO2 or Cr2 O3 ) are deposited between the glass and the nanoparticle. Recently, indium tin oxide and (3-mercaptopropyl)trimethoxysilane (MPTMS) were used as a new adhesion layer. The aim of this work is to compare these six adhesion layers for surface-enhanced Raman scattering sensors by numerical modeling. The near-field and the far-field optical responses of gold nanocylinders on the different adhesion layers are then calculated. It is shown that MPTMS leads to the highest field enhancement, slightly larger than other dielectric materials. We attributed this effect to the lower refractive index of MPTMS compared with the others.